2006
DOI: 10.1177/0892705706063926
|View full text |Cite
|
Sign up to set email alerts
|

The Thermoelectrical Behavior of PEO Films Doped with MnCl2 Salt

Abstract: The poly(ethylene oxide) polymer (PEO) is doped with fine powder of MnCl 2 salt and thin films of thickness (50-150 mm) with salt content (0, 5, 10, 15, and 20 wt%) are obtained. The AC electrical conductivity and dielectric constants are studied as a function of temperature through an impedance technique. It is found that AC conductivity increases and the calculated activation energy decreases with increasing temperature due to enhancement of the ionic conduction in the film bulk. The dielectric constants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The decrease in the dielectric loss with frequency may be attributed to higher induced conductive behavior. [20][21][22][23] Cement polymer composite at T = 30 Jonscher universal power law 15,16,24 based on the aspect of conduction paths accessible for electric charge flow in polymer networks takes the form where A and n are coefficients, s 0 is usually identified as the DC conductivity of the material, and s AC is the frequency-dependent conductivity. At higher frequencies, the conductivity increases as a power of frequency with a power exponent n < 1.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the dielectric loss with frequency may be attributed to higher induced conductive behavior. [20][21][22][23] Cement polymer composite at T = 30 Jonscher universal power law 15,16,24 based on the aspect of conduction paths accessible for electric charge flow in polymer networks takes the form where A and n are coefficients, s 0 is usually identified as the DC conductivity of the material, and s AC is the frequency-dependent conductivity. At higher frequencies, the conductivity increases as a power of frequency with a power exponent n < 1.…”
Section: Resultsmentioning
confidence: 99%
“…These effects enhance the polarization and makes the system not to behave as a solid polymer electrolyte, with enhanced conductivity. 11,21…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The objective of this research is to investigate the electrical and dielectrical behavior of a hybrid system composed using PEO polymer, CaCO 3 , and water traces, that is a fluid system. Our previous studies 5,10,11 on doping of the PEO polymer showed enhancement of the ionic conductivity and dielectric constants due to the formation of doped PEO complexes. Now the question is whether ionic conductivity enhancement can take place in this doped fluid system.…”
Section: Introductionmentioning
confidence: 89%
“…5 On the other hand, the dielectric spectra and relaxation processes of electrolyte polymers and polymer electrolytes have been studied before but the dielectric properties especially the relaxation process and the estimation of relaxation time using Yan and Rhodes model for PEO/NH 4 I electrolytes have not been previously reported. [1][2][3][4][5][6][7][8][9][10][11][12][13] When the dielectric material is exposed to an alternating electric field that is generated by applying a sinusoidal voltage the displacement polarization leads to electric oscillations. The orientational polarization is not a resonant process, because the molecular dipoles have inertia.…”
mentioning
confidence: 99%